Changes in corporate performance associated with bank acquisitions - Cornett, Marcia Millon; Tehranian, Hassan (Journal of Financial Economics, 1992)
This paper examines the post-acquisition performance of large bank mergers between 1982 and 1987. On the whole, the merged banks outperform the banking industry. Their better performance appears to result from improvements in the ability to attract loans and deposits, in employee productivity, and in profitable asset growth. Further, we find a significant correlation between announcement-period abnormal stock returns and the various performance measures, showing that market participants are able to identify in advance the improved performance associated with bank acquisitions.